Cuchillo de Palo - 108 . 108 - Costa, Renate (Estudi Playtime, 2010)
Verzio FF submission To this day, it is as though the number 108 is jinxed in Paraguay. It is not used for houses, cars or hotel-room doors. To call someone by this number is an insult. Nowadays, many Paraguayans don't even know why this is the case. In a very personal documentary, the director investigates the circumstances surrounding the life and death of her mysterious uncle Rodolfo, who was the black sheep of her family. In an interview with her father, Rodolfo's brother, she learns that her uncle was gay. Thanks to her own investigation, she then discovers that he was harshly persecuted because of his sexual orientation by the dictatorial regime of President Alfred Stroessner, who ruled the country from 1954 to 1989. As an intimidating warning in the 1960s, his administration brutally punished 108 people who were included on a special list of presumed homosexuals. This film recounts an entirely forgotten chapter of Paraguayan history.